Lensless multi-spectral holographic interferometry for optical inspection - Agour, Mostafa; Thiemicke, Fabian; Müller, André F.; Bergmann, Ralf B.; Falldorf, Claas (Frontiers in Photonics, 2024)
We explore the principles, implementation details, and performance characteristics of a lensless multi-spectral digital holographic sensor and demonstrate its potential for quality assurance in semiconductor manufacturing. The method is based on capturing multi-spectral digital holograms, which are subsequently utilized to evaluate the shape of a reflective test object. It allows for a compact setup satisfying high demands regarding robustness against mechanical vibrations and thus overcomes limitations associated with conventional optical inspection setups associated with lens-based white light interferometry. Additionally, the tunable laser source enhances the versatility of the system and enables adaptation to various sample characteristics. Experimental results based on a wafer test specimen demonstrate the effectiveness of the method. The axial resolution of the sensor is ±2.5 nm, corresponding to 1σ.